Price integration in the Australian rock lobster industry: implications for management and climate change adaptation1. (14th August 2013) - Norman‐Lόpez, Ana; Pascoe, Sean; Thébaud, Olivier; van, Ingrid; Innes, James; Jennings, Sarah; Hobday, Alistair; Green, Bridget; Plaganyi, Eva
<x xml:space="preserve">Abstract</x> Rock lobster fisheries are Australia's most valuable wild fisheries in terms of both value of production and value of exports. Different states harvest and export different lobster species, with most of the landings being sent to the Hong Kong market. A perception in the Australian lobster industry is that the different species are independent on the export market, such that a change in landings of one species has no impact on the price of the others. This study investigates the market integration of Australian exports to Hong Kong for the four species and different exporting states. Our results indicate all four species and producers/export states are perceived to be substitutes for one another, so that, in the long run, prices paid to operators in the industry will move together. The integrated nature of the Hong Kong export market for Australian lobster suggests that the potential impacts of alternative fisheries management and development strategies at state and species levels cannot be considered in isolation, at least from an economic perspective. In addition, impacts of external shocks affecting production in one state (e.g. climate change) can be expected to affect all Australian lobster fisheries.